Health Care Utilization, Transition Readiness, and Quality of Life: A Latent Class Analysis. (24th November 2020) - Traino, Katherine A; Sharkey, Christina M; Perez, Megan N; Bakula, Dana M; Roberts, Caroline M; Chaney, John M; Mullins, Larry L
Abstract: Objective: To identify possible subgroups of health care utilization (HCU) patterns among adolescents and young adults (AYAs) with a chronic medical condition (CMC), and examine how these patterns relate to transition readiness and health-related quality of life (HRQoL). Methods: Undergraduates ( N = 359; Mage =19.51 years, SD = 1.31) with a self-reported CMC (e.g., asthma, allergies, irritable bowel syndrome) completed measures of demographics, HCU (e.g., presence of specialty or adult providers, recent medical visits), transition readiness, and mental HRQoL (MHC) and physical HRQoL (PHC). Latent class analysis identified four distinct patterns of HCU. The BCH procedure evaluated how these patterns related to transition readiness and HRQoL outcomes. Results: Based on seven indicators of HCU, a four-class model was found to have optimal fit. Classes were termed High Utilization ( n = 95), Adult Primary Care Physician (PCP)-Moderate Utilization ( n = 107), Family PCP-Moderate Utilization ( n = 81), and Low Utilization ( n = 76). Age, family income, and illness controllability predicted class membership. Class membership predicted transition readiness and PHC, but not MHC. The High Utilization group reported the highest transition readiness and the lowest HRQoL, while the Low Utilization group reported the lowest transition readiness and highest HRQoL. Conclusions: The present study characterizes the varying degrees to which AYAs with CMCs utilize health care. Our findings suggest poorer PHC may result in higher HCU, and that greater skills and health care engagement may not be sufficient for optimizing HRQoL. Future research should examine the High Utilization subgroup and their risk for poorer HRQoL.